COMMUNITY PARTICIPATION IN VILLAGE DEVELOPMENT IN KOTA RAJA VILLAGE, AMUNTAI SELATAN SUB-DISTRICT, HULU SUNGAI UTARA REGENCY - muhamad arsyad (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2025)
The problems identified in this study are low attendance in development activities, lack of financial participation, and dependence on village funds. This study aims to examine community participation in village development and the factors that influence it. A qualitative approach was used. Data were collected through in-depth interviews, document analysis, and participant observation. Data sources were selected purposively, involving six participants. Data analysis was conducted using domain and taxonomy techniques. The results show that community participation is fairly good. Good indicators include access to information, involvement in committees, participation in monitoring, feedback, use of facilities, accessibility of results, and improvements in economic, educational, and health activities. Moderately good indicators include attendance at meetings, public consultations, involvement in evaluation, and maintenance activities. Poor indicators include physical attendance and financial participation. The driving factors are group interests and needs, the role of community leaders, the active role of the village government, participation incentives, and understanding the benefits of development. The inhibiting factors are individualism, dependency on incentives, and the perception that responsibilities are handled by others. It is recommended to provide education, apply intensive engagement strategies, strengthen togetherness and transparency, and encourage people to make time for social activities